2014
DOI: 10.1155/2014/682010
|View full text |Cite
|
Sign up to set email alerts
|

SEA Antagonizes the Imatinib-Meditated Inhibitory Effects on T Cell Activation via the TCR Signaling Pathway

Abstract: The BCR-ABL kinase inhibitor imatinib is highly effective in the treatment of chronic myeloid leukemia (CML). However, long-term imatinib treatment induces immunosuppression, which is mainly due to T cell dysfunction. Imatinib can reduce TCR-triggered T cell activation by inhibiting the phosphorylation of tyrosine kinases such as Lck, ZAP70, LAT, and PLCγ1 early in the TCR signaling pathway. The purpose of this study was to investigate whether the superantigen SEA, a potent T cell stimulator, can block the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(42 reference statements)
0
2
2
Order By: Relevance
“…In addition, unlike SEA, PHA cannot induce the secretion of IL-2 in CCRF-CEM T-cells with or without Raji B-cells as accessory cells as shown in Figure 6a. These results contrast to the findings of Wang et al [23] who reported that SEA alone in the absence of accessory cells could activate a T-cell clone.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, unlike SEA, PHA cannot induce the secretion of IL-2 in CCRF-CEM T-cells with or without Raji B-cells as accessory cells as shown in Figure 6a. These results contrast to the findings of Wang et al [23] who reported that SEA alone in the absence of accessory cells could activate a T-cell clone.…”
Section: Resultscontrasting
confidence: 99%
“…Accessory cells are necessary for the reduction of TCR Vβ9 protein expression on CCRF-CEM T-cells using SEA but not using the plant lectin phytohemagglutinin (PHA). This is contrary to the findings of Wang et al [23] in which it was reported that SEA alone, without any co-stimulatory molecule, could elicit a response from a T-cell clone in the absence of any accessory cells that process SEA into antigenic peptides and present the fragmented SEA components via their major histocompatibility complexes (MHCs) to the T-cell. Our results in Figure 4 stand in contrast to that finding and reveal that the presence of Raji B-cells bearing co-stimulatory molecules are essential to generate a secondary cellular signal required for this effect.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…The TEC model was used as the basis for the following experiments. All rats were divided into five groups ( n = 5 per group; Figure ): the control group, the zymosan A (Sigma‐Aldrich)‐treated group (0.1 mg, intraperitoneal injection to induce inflammation; Hartog, Cozijnsen, de Vrij, & Garssen, ), the 5‐aminoisoquinolinone hydrochloride (Sigma‐Aldrich)‐treated group (3 mg/kg, tail vein injection to reduce inflammation; Di Paola et al, ), the imatinib (Sigma‐Aldrich)‐treated group (50 mg/kg, tail vein injection to inhibit the proliferation of T cells; Cwynarski et al, ; Wang, Yan, Chen, Lin, & Li, ), and the CD8+ T cell‐injected group (1 ml of T cells isolated from the peripheral blood and administered via the tail vein).…”
Section: Methodsmentioning
confidence: 99%